Factors associated with the use of dental services in older adults in Peru - Bryan Alexis Cossio-Alva; Rubén Espinoza Rojas; Miguel Angel Ruiz-Barrueto; Giancarlo Becerra Atoche; Christian R. Mejia; Ibraín Enrique Corrales-Reyes (PLoS ONE, 2025)
Background The use of dental services by older adults in Peru faces various challenges that impact both their oral and overall health. Several factors play a crucial role in obtaining adequate dental care. Aims To evaluate the factors associated with the use of dental services in older adults in Peru. Methods This study was an observational, analytical, and cross-sectional investigation that utilized data from multiple years (2018–2022) of the Demographic and Family Health Survey (ENDES, by its Spanish acronym). The use of dental services was assessed through a specific survey question and analyzed in association with various socio-demographic variables, employing both descriptive and analytical statistical methods. Results In the multivariable analysis, the likelihood of not utilizing dental services was higher among men aPR: 1.53 (95% CI: 1.45–1.61), those without health insurance aPR: 1.44 (95% CI: 1.36–1.53), those who self-identified as other races aPR: 1.22 (95% CI: 1.13–1.33), Afro-descendants aPR: 1.10 (95% CI: 1.01–1.19), whites aPR: 1.12 (95% CI: 1.01–1.25) according to education level, those with a physical limitation aPR: 1.24 (95% CI: 1.15–1.33), and increased as they were poorer; it was lower among the rich but more pronounced among the middle-income, poor, and very poor, adjusted for five variables. Conclusion It was reported that 15% of older adults did not use dental services, and this was associated with significant socio-demographic variables.